Workshop on Ethnic Integration in Public Universities - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2004)
On 22nd June 2004, IPPTN and University Sains Malaysia, with the cooperation of the Department of Higher Education, held a workshop on ethnic integration in Public Universities study at Equatorial Hotel, Penang. Officiated by the Chief Secretary, Ministry of Higher Education, Y. Bhg. Dato’ Dr. Mohd. Yahya Nordin, the workshop was intended to present major findings obtained from the study and to gather feedback from participants.